Desenvolvimento de um compósito inseticida-fertilizante microencapsulado para promover o aumento de produtividade agrícola - Durango, Luis Guillermo Cuadrado (Universidade Federal de São Carlos, 2017)
The main objective of this work was to develop a bioinsecticide-fertilizer model for pest insect control, formulated with extract of Azadirachta indica A. Juss. and humic acids as polymer matrix and fertilizer agent. Formulation methods with different natural polymeric matrices such as lignin and poly(ε-caprolactone) were developed to compare yield, cost, environmental advantages and efficacy. Among the proposed nano/microencapsulation methods, the main one was the precipitation of the preformed polymer. The extracts and products were quantified by validating an analytical method to quantify the azadirachtin content by High Efficiency Liquid Chromatography (HPLC). Subsequently, different nano/micro characterization methods were used to evaluate the stability of nano/microparticles in colloidal suspension, investigating the stability and properties of the natural nano/microencapsulated product, particle size, zeta potential, distribution of polymer molar mass, the content of the active compound before and after the encapsulation process, and the pH from dispersion medium. The formulation promoted gains in UV-light and thermal stability of approximately 50% to nano/microencapsulated azadirachtin, maintaining the efficient insecticide action to Spodoptera frugiperda. The data obtained in biological bioassays showed a mortality rate higher than 50% to the formulated products compared to the nonencapsulated Azadirachta indica A. Juss extract as control in the mean evaluation of 10 days. Finally, the evaluation of the duality of the function of humic acids in the encapsulation process and fertilizer action were significantly relevant, providing average germination in corn plants of 89.1±0.1%, and in the function of polymeric with yields above 70.3±0.1%. The results promoted a micro/nanoencapsulated product formulated with humic acids as a biodegradable polymer matrix and with fertilizer applicability, obtaining a final product, maintaining the stability of the active ingredient and efficient insecticide action against Spodoptera frugiperda, incursion at the development of new micro/nanotechnological strategies for the control of insect pests, reducing the negative impact on the environment medium.
Microencapsulated insecticide-fertilizer composite development to promote increased agricultural productivity
Keywords: Nanoencapsulamento polimérico; Biopesticidas; Azadirachta indica A. Juss.; Azadirachtina A; Ácidos húmicos; Spodoptera frugiperda; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::FERTILIDADE DO SOLO E ADUBACAO; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::QUIMICA DO SOLO; CIENCIAS EXATAS E DA TERRA::QUIMICA; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA::INSTRUMENTACAO ANALITICA; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA::EVOLUCAO, SISTEMATICA E ECOLOGIA QUIMICA; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA::QUIMICA DOS PRODUTOS NATURAIS; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA